2020
DOI: 10.1007/s11682-020-00281-y
|View full text |Cite
|
Sign up to set email alerts
|

Abberant inverted U-shaped brain pattern and trait-related retinal impairment in schizophrenia patients with combined auditory and visual hallucinations: a pilot study

Abstract: Schizophrenic patients often experience auditory hallucinations (AHs) and visual hallucinations (VHs). However, brain and retinal alterations associated with combined AHs and VHs in schizophrenic patients are unknown. This study aimed o investigate brain and retinal alterations in first episode untreated schizophrenic patients with combined AHs and VHs (FUSCHAV). FUSCHAV patients (n = 120), divided into four groups according to severity of AH and VH symptoms, were compared to healthy controls (n = 30). Gray ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…This will help develop comprehensive treatment strategies, such as antipsychotic and brain stimulation therapies (e.g., neural feedback techniques, rTMS, tDCS, AVATAR), to normalize the brain alterations associated with AVHs and depressive symptoms (Bohlken et al., 2017). Hence, in agreement with previous studies, we have shown that functional alterations in first‐episode schizophrenia patients with AVHs have an “inverted U‐shaped” pattern, in which network connectivity is initially increased, followed by a reduction in connectivity (Zhuo, Xiao, et al, 2020).…”
Section: Depressive Symptoms In Schizophreniasupporting
confidence: 92%
“…This will help develop comprehensive treatment strategies, such as antipsychotic and brain stimulation therapies (e.g., neural feedback techniques, rTMS, tDCS, AVATAR), to normalize the brain alterations associated with AVHs and depressive symptoms (Bohlken et al., 2017). Hence, in agreement with previous studies, we have shown that functional alterations in first‐episode schizophrenia patients with AVHs have an “inverted U‐shaped” pattern, in which network connectivity is initially increased, followed by a reduction in connectivity (Zhuo, Xiao, et al, 2020).…”
Section: Depressive Symptoms In Schizophreniasupporting
confidence: 92%
“…In Parkinson's disease, one study demonstrated a relationship between RNFL thinning and VH ( 153), but a second study found no evidence for such a link (154). A recent study in schizophrenia (155,156) indicated that four separate samples of patients with both auditory and visual hallucinations of at least moderate severity were characterized by significant macula and RNFL thinning relative to a control group. The lack of a control group of patients with auditory hallucinations only and/or no hallucinations precludes a definitive conclusion regarding specific relationships with VH, however.…”
Section: Potential Retinal Contributions To Vh and Visual Distortions In Schizophreniamentioning
confidence: 99%
“…When the time difference is zero, the reflectance is maximum and it is called constructive interference. is means the monochromatic signal intensity fringes are in phase only for zero time [23][24][25][26][27][28].…”
Section: Simulations Of Oct In a Michelson Interferometermentioning
confidence: 99%